SOCIO-STYLISTICS OF GUS BAHA’S SERMONS - Aang Fatihul Islam; Dian Anik Cahyani (STKIP PGRI Jombang, 2022)
As a result of this realization, a new study of Gus Baha's preaching discourse, particularly on Java, is required. This study serves a strategic purpose as a foundation for future research and, more broadly, as a reference for preaching knowledge. There are three approaches in examining sermons, according to past expert research: language, socio-culture, and religiosity or religion. As a result, the goal of this study is to describe Gus Baha's sermon presented on Java Island as a discourse, as well as its stylistics features in relation to its rules environment and how the language choice of Gus Baha send his sermon to audiences. This study applied. This is study applied qualitative method with a real-life context that describes qualitatively in words rather than numbers or statistics, using content analysis as research design. For the analysis of the data, specific finding have been made. The contextual features show that the audience of Gus Baha’s sermons are two kind namely lay society and intellectual or government offices, so that in the application of the contextual features also different. In the context of lay society which describe in ‘Toleransi Terhadap Non Muslim Menurut Gus Dur’ sermon Gus Baha in fact dominantly used Javanese language and also Pesantren culture, but on the contrary in ‘Haul K.H. Wahab Hasbullah ke-49’ sermon Gus Baha dominantly used Bahasa Indonesia and formal language, it is because the audience is in the kind of overment office and intellectual society, although there some santri there, but Gus Baha prefer choose formal language so that can be understood by all of the audiences. In the context of the application of lexyco sintaxtical choice Gus Baha applied climax, Cynicism and paradox and in the context of the application of lexico syntaxtical pattern Gus Baha applied repetition, enumeration, anaphora, and rhetorical question. in Both of sermons Gus Baha dominantly used enumeration as the general strategy to give clear understanding to audiences by sole some crucial problem in society through his clever sermon.